2003
DOI: 10.1093/emboj/cdg308
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of Rev3, the catalytic subunit of pol  in maintaining genome stability in vertebrates

Abstract: Translesion DNA synthesis (TLS) and homologous DNA recombination (HR) are two major postreplicational repair (PRR) pathways. The REV3 gene of Saccharomyces cerevisiae encodes the catalytic subunit of DNA polymerase ζ, which is involved in mutagenic TLS. To investigate the role of REV3 in vertebrates, we disruped the gene in chicken DT40 cells. REV3−/− cells are sensitive to various DNA‐damaging agents, including UV, methyl methanesulphonate (MMS), cisplatin and ionizing radiation (IR), consistent with its role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
191
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(209 citation statements)
references
References 76 publications
16
191
1
Order By: Relevance
“…In particular, they have also been implicated in the regulation of translesion polymerases in postreplication repair (16,17), but the function of these polymerases in other genetic processes in eukaryotes may also be regulated by different means, i.e., independently of the Rad6 pathway (18)(19)(20). In the present study, we show that the crucial initiator factor of the Rad6 pathway, Rad18, plays a role during somatic hypermutation in the DT40 B cell line.…”
mentioning
confidence: 48%
“…In particular, they have also been implicated in the regulation of translesion polymerases in postreplication repair (16,17), but the function of these polymerases in other genetic processes in eukaryotes may also be regulated by different means, i.e., independently of the Rad6 pathway (18)(19)(20). In the present study, we show that the crucial initiator factor of the Rad6 pathway, Rad18, plays a role during somatic hypermutation in the DT40 B cell line.…”
mentioning
confidence: 48%
“…Further, overexpression of REV1 in ovarian tumor lines led to some resistance to cisplatin and increased mutagenic frequency compared to parental lines [64]. Among DNA repair gene knockouts in chicken DT40 cells, rev3 mutants are the most sensitive to cisplatin of any single mutant examined [65]. Vertebrate REV3 and REV1 apparently play a more important role in cellular tolerance of some DNA-damaging agents than others.…”
Section: Consequences Of Rev3l Rev1 and Rev7 Reduction In Human Cellmentioning
confidence: 98%
“…Single disruption mutants of these genes were reported to have increased frequencies of sister chromatid exchange, both spontaneously and in response to 4-nitroquinolone-1-oxide and UV radiation [65,66]. An independent study using the same REV3L-disrupted cell line found that sister chromatid exchanges were still induced normally by 4-nitroquinolone-1-oxide, but were not induced by treatment with mitomycin C or cisplatin [67].…”
Section: Role Of Pol ζ In Interstrand Crosslink Repair and Recombinationmentioning
confidence: 99%
“…To assess the role of SLX4 in HR-dependent double-strand break (DSB) repair, we exposed the SLX4 −/− tetSLX4 cells to γ rays (2 Gy) at 48 h after the addition of doxycycline, harvested mitotic cells 3 h later, and counted the number of chromosomal breaks. Using this protocol, we were able to selectively evaluate HRdependent DSB repair in the G 2 phase, because only cells irradiated in G 2 and not in S enter mitosis within 3 h, and also because cells in the G 2 phase preferentially use HR for DSB repair (31,32). In WT cells, ionizing radiation induced predominantly chromatid-type breaks (i.e., breaks in one sister chromatid).…”
Section: Slx4 Is Essential For Cell Proliferationmentioning
confidence: 99%